Kepedulian Muslim Perkotaan terhadap Kehalalan Makanan Produk Pengusaha Mikro Kecil (Kasus pada Masyarakat Muslim Minoritas di Kota Kupang, NTT) - Yuwono, Dandung Budi (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2017)
As a country with a Muslim majority, it is not uncommon for the state to protect the Islamic community from consuming food, drugs and cosmetics that originate from non-halal substances and ingredients. In reality, the state has yet to provide certain guarantee regarding the halal status of a product in accordance to the Islamic law. There are still very few food products from the micro and small industries that posses and propose for halal certification. Micro and small entrepreneurs as of current remain unconcerned regarding the halal status of their products, despite the availability of assistance in the certification process. What about the case in which a minority Muslim community resides amidst a community of non-muslim majority with its local regulation and character in the city of Kupang? For that reason, this explorative research which employed a mixed-method approach will attempt to answer the following questions: (1) what are the concern of urban Muslim community in the city of Kupang regarding the halal status of micro/small business food products; and (2) what factors influence the concern of the Muslim community in the city of Kupang regarding the halal status of micro/small business food products. The objectives of this research are: (1) obtain an outlook on the concern of Muslim community in the city of Kupang regarding the halal status of micro/small business food products; (2) obtain understanding on actions undertaken based on the concern of Muslim community in the city of Kupang regarding the halal status of micro/small business food products; and (3) to identify the factors influencing the concern of Muslim community in the city of Kupang regarding the halal status of micro/small business food products. The research result shows a high concern of Muslim community in the city of Kupang regarding the halal status of micro/small business food products. It is proven that as much as 77% of respondents stated they always checked the halal label of packaged food, 48% of respondents stated that they always asked fast food vendors whether lard based oil is used, 86% of respondents said that they would speak fairly if they knew that a chicken vendor is selling meat that has gone bad, 97% of respondents said they refused to continue their purchase when entering a restaurant offering menu of chicken, goat, or beef that is processed side by side with pork, and as much as 88% of respondents stated that they would report a seller who mixes chicken or other meat with pork. The high level of concern demonstrated by the Muslim community in the city of Kupang is caused by a sociological factor, wherein being a minor community living in a community with differing religious norms has in fact triggered the community’s awareness in the importance of halal products.